2009
DOI: 10.1261/rna.1668309
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for sequences upstream of and downstream from Physarum editing sites

Abstract: RNAs in the mitochondria of Physarum polycephalum contain nonencoded nucleotides that are added during RNA synthesis. Essentially all steady-state RNAs are accurately and fully edited, yet the signals guiding these precise nucleotide insertions are presently unknown. To localize the regions of the template that are required for editing, we constructed a series of chimeric templates that substitute varying amounts of DNA either upstream of or downstream from C insertion sites. Remarkably, all sequences necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…This is consistent with the experimental finding of Rhee et al (2009), which determined that information in the 9 bp upstream of and downstream from an insertion site are necessary for proper insertional editing.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the experimental finding of Rhee et al (2009), which determined that information in the 9 bp upstream of and downstream from an insertion site are necessary for proper insertional editing.…”
Section: Resultssupporting
confidence: 91%
“…Recently, the P. polycephalum mitochondrial RNA polymerase has been cloned (Miller et al 2006), and it has been found to add non-DNA-templated nucleotides to the 39 end of RNAs (Miller and Miller 2008). Using chimeric templates and in vitro mitochondrial transcription elongation complexes Rhee et al (2009) demonstrated the importance of 9 base pairs (bp) to either side of C insertion sites in directing this type of editing event.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work provides strong evidence for the importance of the 9 bp template sequence immediately upstream and downstream of insertion sites in directing proper editing (Rhee et al 2009). These results explained observations of a minimum distance of 9 bp between editing sites (Miller et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial RNA polymerase has been cloned and shown to indeed add nonencoded nucleotides to the 3 0 end of nascent RNAs [178,179]. Investigating the mechanisms that guide and control the cotranscriptional insertions of nucleotides has revealed that approximately 9 bp flanking the insertion sides on both sides of the DNA template play important roles [180][181][182][183][184]. How many further biochemically distinct and independent activities of RNA editing (e.g., of a deamination type for the C-to-U conversions) actually exist in myxomycetes is currently an open question addressed with different in vitro systems [185].…”
Section: X?mentioning
confidence: 99%